Fiber-reinforced dual cross-linked network conductive hydrogel and method of making the same

CN122917346APending Publication Date: 2026-10-16TIANJIN UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611332178.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,该专利未涉及细菌纤维素化学改性增强策略,也未公开导电水凝胶的拉伸性能及应变传感性能参数,难以体现材料在高力学性能与稳定柔性传感方面的综合性能

Benefits of technology

[0014]上述纤维增强的双交联网络导电水凝胶可应用在柔性传感与智能生物电子材料领域。将所述水凝胶作为传感元件集成于可穿戴设备中,可实时监测压力、应变与人体运动信号,并对监测信号进行高灵敏度响应和稳定输出。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917346A_ABST
    Figure CN122917346A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of fiber reinforced double crosslinking network conductive hydrogel and its preparation method.It is characterized in that the hydrogel is by polymer matrix, functionalized fiber reinforced component, conductive nanometer component and crosslinking system constitute three-dimensional network structure, wherein functionalized fiber reinforced component is thiolated bacterial cellulose and other fiber materials, conductive nanometer component is MXene, carbon nanotube or silver nanowire etc., by light crosslinking or ion crosslinking etc. Stable composite network is structured.The hydrogel of the present application has excellent flexibility, mechanical stability and conductive sensing performance.Compressive strength can reach 1-1000 kPa, recovery rate is greater than 80% under 50%-90% compression strain, electrical conductivity is 10 ‑4 -10 S·m ‑1 ;Resistance signal response is stable in cyclic tensile or compression test, and cyclic durability is excellent.The preparation process of the present application is mild and controllable, and can be used in the field of flexible sensor, wearable monitoring and intelligent bioelectronic device etc..
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flexible sensing and intelligent bioelectronic materials technology, and relates to a fiber-reinforced double cross-linked network conductive hydrogel and its preparation method, focusing on the design and preparation of highly sensitive conductive hydrogel sensing materials. This hydrogel possesses excellent conductivity, flexibility, and mechanical stability, enabling real-time monitoring of pressure and strain, and is suitable for applications such as flexible sensors, electronic skin, and intelligent bioelectronic devices. Background Technology

[0002] With the rapid development of intelligent manufacturing, wearable devices, and human health monitoring technologies, sensors have been widely used in fields such as environmental perception, human-computer interaction, and physiological signal monitoring. Traditional rigid sensors are usually made of hard materials such as metals and semiconductors. Although they have high signal response and stability, their lack of flexibility and limited deformation adaptability make them difficult to meet the application requirements of human motion monitoring and complex curved surface fitting.

[0003] In recent years, flexible sensors have attracted widespread attention in the fields of electronic skin, wearable health monitoring, and intelligent human-computer interaction due to their excellent flexibility, stretchability, and high adaptability to the human body interface. As a core functional material of flexible sensors, flexible conductive hydrogels possess a soft structure, good ductility, and electron transport capabilities, effectively converting external mechanical stimuli into electrical signals. However, existing conductive hydrogels typically rely on a single polymer network or a simple nano-conductive filler composite structure. Under repeated stretching, bending, and other mechanical deformations, the internal network structure is easily damaged, leading to discontinuous conductive pathways, resistance signal drift, and decreased cycle stability, making it difficult to meet the requirements of high-reliability motion sensing. Therefore, developing a flexible conductive hydrogel with an enhanced network structure, stable conductive pathways, and excellent cycle durability is of great significance for improving the signal stability and practical application reliability of flexible sensors.

[0004] Chinese patent publication CN111303449A discloses a bacterial cellulose / MXene conductive hydrogel and its preparation method, which constructs a conductive network using bacterial cellulose and MXene. This patent uses unmodified bacterial cellulose, and the interfacial bonding mainly relies on physical interactions. The mechanical properties and network stability need improvement, and it does not address research on fiber-reinforced double-crosslinked networks or flexible strain sensing performance.

[0005] Chinese patent publication CN118667189A discloses a photocurable biomass-based dual-network conductive hydrogel and its preparation method. The dual network is constructed using GelMA and CMCS, and MXene@TA@PEDOT:PSS is introduced to improve conductivity. However, this patent does not address the bacterial cellulose chemical modification enhancement strategy, nor does it disclose the tensile properties and strain sensing performance parameters of the conductive hydrogel, making it difficult to demonstrate the material's comprehensive performance in terms of high mechanical properties and stable flexible sensing.

[0006] Non-patent literature (ACS Applied Electronic Materials, 2024) reports a flexible strain sensor using a polyacrylamide (PAM) / LiCl / MXene conductive hydrogel. This conductive hydrogel uses polyacrylamide as the matrix material, which has limited biocompatibility and biodegradability. Furthermore, it does not employ natural fiber reinforcement or a double cross-linked network structure, nor does it involve methods for chemically modifying bacterial cellulose to enhance interfacial bonding. Therefore, it is difficult to balance mechanical properties, biosafety, and long-term stability. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention aims to provide a fiber-reinforced double cross-linked network conductive hydrogel and its preparation method. This hydrogel not only possesses excellent conductivity and good mechanical strength, but also exhibits outstanding flexibility and structural stability, enabling real-time monitoring of pressure and strain. Compared with conductive hydrogel materials reported in other works, the overall performance of this invention is significantly improved.

[0008] To achieve the above objectives, the technical solution of the present invention is as follows: A fiber-reinforced double cross-linked conductive hydrogel and its preparation method are disclosed. The hydrogel comprises a polymer matrix, functionalized fiber reinforcing components, conductive nano-components, and a cross-linking system. First, the polymer matrix, functionalized fiber reinforcing components, and conductive nano-components are dispersed in a solvent to form a uniform precursor system. Then, the cross-linking system is added. After mixing, degassing, and curing, the polymer matrix forms a cross-linked network. Simultaneously, the functionalized fiber reinforcing components form an interfacial chemical bond with the polymer matrix and synergistically construct a fiber-reinforced double cross-linked conductive network with the conductive nano-components, thereby obtaining a conductive hydrogel with good mechanical properties, conductivity, and flexible sensing properties.

[0009] The polymer matrix mentioned above refers to one or more of the following: methacrylamide gelatin (GelMA), hyaluronic acid methacrylamide hyaluronic acid (HAMA), polyethylene glycol diacrylate (PEGDA), and their derivatives; the fiber reinforcing component refers to one or more of the following: thiolated bacterial cellulose, bacterial cellulose, cellulose nanofibers (CNF), cellulose nanocrystals (CNC), carboxymethyl cellulose, and their modified products; the conductive nanocomponent refers to one or more of the following: MXene, graphene oxide, reduced graphene oxide, graphene, carbon nanotubes, silver nanowires, conductive polymer nanomaterials, and their composite materials.

[0010] Furthermore, the thiolated bacterial cellulose is obtained by reacting bacterial cellulose with a silane coupling agent, wherein the silane coupling agent is γ-mercaptopropyltrimethoxysilane (MPTMS) or γ-mercaptopropyltriethoxysilane (MPTES), and the amount of silane coupling agent added is 1%-30% of the mass of bacterial cellulose, preferably 1%-20%; the thiolation reaction is obtained by dispersing bacterial cellulose in ethanol, water or an ethanol-water mixture and reacting it with the silane coupling agent for 1-24 hours.

[0011] Furthermore, the mass ratio of the polymer matrix, functionalized fiber reinforcing component, and conductive nano-component is (5-20):(0.1-5):(0.01-2), and the amount of conductive nano-component added accounts for 0.1%-20% of the mass of the polymer matrix, preferably 0.5%-10%.

[0012] Furthermore, the preparation method of the conductive hydrogel is as follows: after uniformly mixing the polymer matrix, functionalized fiber reinforcing component and conductive nano component according to the mass ratio, a photoinitiator is added to prepare a precursor solution, which is heated in a water bath at 40-80℃ for 10-120 min, then centrifuged at 500-3000 r / min for 5-30 min to remove air bubbles, and then photocrosslinked and cured by irradiation with ultraviolet light at a wavelength of 365-405 nm for 10 s-60 min to obtain a fiber-reinforced double crosslinked network conductive hydrogel.

[0013] Furthermore, the hydrogel has a compressive strength of 1-1000 kPa, a recovery rate of over 80% after compressive strain reaches 50%-90%, and an electrical conductivity of 10. -4 -10 S·m -1 .

[0014] The aforementioned fiber-reinforced, double-crosslinked conductive hydrogel can be applied in the fields of flexible sensing and smart bioelectronic materials. Integrating this hydrogel as a sensing element into wearable devices allows for real-time monitoring of pressure, strain, and human motion signals, providing a highly sensitive response and stable output to the monitored signals. Attached Figure Description

[0015] Figure 1 This is a scanning electron microscope (SEM) image of the MXene nanosheets used in Example 1 of this invention. As can be seen from the image, MXene exhibits a typical two-dimensional layered sheet structure with well-exfoliated sheets and minimal interlayer stacking. It possesses a large specific surface area and abundant surface active sites, which facilitates its uniform distribution in the polymer matrix and the formation of a continuous conductive network. Therefore, it can be used as a conductive nanocomponent in conductive hydrogels.

[0016] Figure 2 The image shows the Fourier transform infrared (FTIR) spectra of bacterial cellulose (BC) and thiolated bacterial cellulose (TBC) from Example 2 of this invention. Compared to unmodified bacterial cellulose, thiolated bacterial cellulose shows a higher wavelength at 3351 cm⁻¹. -1 2924 cm -1 1607 cm -1 and 1059 cm -1 The significant change in the nearby characteristic absorption peaks indicates that the thiolation modification was successful. Functional groups have been introduced into the surface of bacterial cellulose, improving its surface activity and interfacial reactivity, which is beneficial for enhancing its chemical bonding with the polymer matrix, thereby constructing a stable fiber-reinforced double crosslinked network.

[0017] Figure 3 The figure shows the tensile stress-strain curves of the GelMA / BC / AgNWs and GelMA / TBC / AgNWs composite conductive hydrogels in Example 3 of this invention. As can be seen from the figure, the introduction of thiolized bacterial cellulose significantly improved the tensile strength and elongation at break of the composite conductive hydrogel, indicating that thiolization modification enhanced the interfacial interaction between bacterial cellulose and the GelMA matrix, thereby improving the mechanical properties and structural stability of the composite conductive hydrogel.

[0018] Figure 4 This is a test curve for the cyclic sensing performance of the 1% MXene composite conductive hydrogel prepared in Example 4 of this invention. The horizontal axis represents time, and the vertical axis represents the rate of change of relative resistance. Under multiple cyclic tests, the hydrogel's resistance response signal is stable and repeatable, confirming that the conductive hydrogel has good sensing cyclic stability. Example

[0019] (1) Weigh 0.5 g of methacrylamide gelatin (GelMA) and add it to 5 mL of deionized water. Stir magnetically for 20 min in a 60 ℃ water bath to fully dissolve the GelMA.

[0020] (2) Add 0.0025 g of photoinitiator Irgacure 2959, 0.05 g of thiolated bacterial cellulose and 0.02 g of MXene nanosheets to the obtained GelMA solution, and continue stirring at 60 °C for 30 min to make the thiolated bacterial cellulose and MXene uniformly dispersed in the GelMA prepolymer system.

[0021] (3) Place the mixture in a centrifuge and centrifuge at 2000 r / min for 10 min to remove bubbles.

[0022] (4) The obtained precursor liquid was injected into the mold and irradiated with 365 nm ultraviolet light for 30 min to cause photocrosslinking of GelMA. The three-dimensional composite structure was constructed by the thiolized cellulose reinforcement network and the MXene conductive network.

[0023] (5) After soaking in deionized water for 24 h, a flexible conductive hydrogel based on a functionalized fiber-reinforced network was obtained. Example

[0024] (1) Weigh 0.5 g of methacrylamide gelatin (GelMA) and add it to 5 mL of phosphate buffer (PBS). Stir magnetically for 30 min in a 50°C water bath to fully dissolve the GelMA.

[0025] (2) Add 0.0025 g of photoinitiator Irgacure 2959, 0.03 g of thiolated bacterial cellulose and 0.01 g of carbon nanotubes (CNTs) to the obtained GelMA solution, and sonicate at 50 °C for 15 min to make the thiolated bacterial cellulose and carbon nanotubes uniformly dispersed in the GelMA prepolymer system.

[0026] (3) Place the mixture in a centrifuge and centrifuge at 1500 r / min for 15 min to remove bubbles.

[0027] (4) The obtained precursor liquid was injected into the mold and irradiated with 365 nm ultraviolet light for 20 min to cause photocrosslinking of GelMA. A three-dimensional composite structure was constructed by the synergistic construction of the thiolized cellulose reinforcement network and the carbon nanotube conductive network.

[0028] (5) After soaking in deionized water for 24 h, a flexible conductive hydrogel based on a functionalized fiber-reinforced network was obtained. Example

[0029] (1) Weigh 0.5 g of methacrylamide gelatin (GelMA) and add it to 5 mL of deionized water. Stir magnetically for 20 min in a 60 ℃ water bath to fully dissolve the GelMA.

[0030] (2) Add 0.0025 g of photoinitiator Irgacure 2959, 0.04 g of thiolated bacterial cellulose and 0.015 g of silver nanowires (AgNWs) to the obtained GelMA solution, and continue stirring at 60 °C for 30 min to make the thiolated bacterial cellulose and silver nanowires uniformly dispersed in the GelMA prepolymer system.

[0031] (3) Place the mixture in a centrifuge and centrifuge at 2000 r / min for 10 min to remove bubbles.

[0032] (4) The obtained precursor liquid was injected into the mold and irradiated with 365 nm ultraviolet light for 25 min to cause photocrosslinking of GelMA. The three-dimensional composite structure was constructed by the thiolized cellulose reinforcement network and the silver nanowire conductive network.

[0033] (5) After soaking in deionized water for 24 h, a flexible conductive hydrogel based on a functionalized fiber-reinforced network was obtained. Example

[0034] (1) Weigh 0.3 g GelMA and 0.2 g methacrylamide hyaluronic acid (HAMA), add 5 mL of deionized water, and stir at 60 °C for 30 min to obtain GelMA / HAMA mixed prepolymer solution.

[0035] (2) Add 0.003 g Irgacure 2959, 0.05 g thiolated bacterial cellulose and 0.01 g MXene nanosheets to the solution obtained in step (1), and continue stirring for 30 min to make the components evenly dispersed.

[0036] (3) The resulting mixture was centrifuged at 2000 r / min for 15 min to remove bubbles.

[0037] (4) Place the degassed precursor liquid in a mold and irradiate it with 365 nm ultraviolet light for 40 min to complete photocrosslinking, and obtain GelMA / HAMA / thiolized bacterial cellulose / MXene composite conductive hydrogel.

[0038] (5) The obtained hydrogel was washed with deionized water for 24 h to obtain a multifunctional conductive hydrogel. Example

[0039] (1) Weigh 0.5 g of polyethylene glycol diacrylate (PEGDA) and add it to 5 mL of deionized water. Stir at 50 °C for 20 min to fully dissolve PEGDA.

[0040] (2) Add 0.005 g Irgacure 2959, 0.05 g thiolated bacterial cellulose and 0.02 g silver nanowires (AgNWs) to the solution obtained in step (1) and continue stirring for 30 min.

[0041] (3) Centrifuge the mixed solution obtained in step (2) at 2000 r / min for 10 min to remove air bubbles.

[0042] (4) Place the precursor liquid obtained in step (3) under 365 nm ultraviolet light for 20 min to allow PEGDA to crosslink and cure.

[0043] (5) After soaking and cleaning the hydrogel obtained in step (4) with deionized water, a PEGDA / thiolized bacterial cellulose / AgNWs composite conductive hydrogel is obtained.

[0044] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Any equivalent substitutions or adjustments made by those skilled in the art to the material composition, mass ratio, and preparation process parameters without departing from the technical concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. A fiber-reinforced double cross-linked network conductive hydrogel and its preparation method, characterized in that, The hydrogel is a three-dimensional network structure formed by cross-linking a polymer matrix, functionalized fiber reinforcing components, and conductive nano-components; the polymer matrix and the functionalized fiber reinforcing components are covalently cross-linked, and the conductive nano-components are uniformly dispersed in the three-dimensional network structure; The hydrogel is flexible and conductive.

2. The fiber-reinforced double-crosslinked network conductive hydrogel and its preparation method according to claim 1, characterized in that, The polymer matrix is ​​one or more of gelatin, methacrylamide gelatin (GelMA), methacrylamide hyaluronic acid (HAMA), polyethylene glycol diacrylate (PEGDA), and their derivatives; the fiber reinforcing component is one or more of thiolized bacterial cellulose, bacterial cellulose, cellulose nanofibers (CNF), carboxymethyl cellulose, and their modified products; the conductive nanocomponent is one or more of MXene, graphene oxide, reduced graphene oxide, graphene, carbon nanotubes, silver nanowires, conductive polymer nanomaterials, and their composite materials.

3. The fiber-reinforced double cross-linked network conductive hydrogel and its preparation method according to claim 1, characterized in that, The thiolated bacterial cellulose is obtained by reacting bacterial cellulose with a silane coupling agent, wherein the silane coupling agent is γ-mercaptopropyltrimethoxysilane (MPTMS) or γ-mercaptopropyltriethoxysilane (MPTES).

4. The fiber-reinforced double cross-linked network conductive hydrogel and its preparation method according to claim 1, characterized in that, The amount of the silane coupling agent added is 1%-30% of the bacterial cellulose mass, preferably 1%-20%.

5. The fiber-reinforced double cross-linked network conductive hydrogel and its preparation method according to claim 1, characterized in that, The thiolized bacterial cellulose is obtained by dispersing bacterial cellulose in ethanol, water, or an ethanol-water mixture and reacting it with a silane coupling agent for 1-24 h.

6. The fiber-reinforced double cross-linked network conductive hydrogel and its preparation method according to claim 1, characterized in that, The mass ratio of the polymer matrix, functionalized fiber reinforcement component and conductive nanocomposition is (5-20):(0.1-5):(0.01-2).

7. The fiber-reinforced double-crosslinked network conductive hydrogel and its preparation method according to claim 1, characterized in that, The conductive nanocomponent is added at a rate of 0.1%-20% of the polymer matrix mass, preferably 0.5%-10%.

8. The fiber-reinforced double cross-linked network conductive hydrogel and its preparation method according to claim 1, wherein a polymer matrix, functionalized fiber reinforcing components and conductive nano-components are mixed uniformly according to a mass ratio, a photoinitiator is added to prepare a precursor solution, the solution is heated in a water bath at 40-80 °C for 10-120 min, then centrifuged at 500-3000 r / min for 5-30 min to remove air bubbles, and then photocrosslinked and cured by irradiation with ultraviolet light at a wavelength of 365-405 nm for 10 s-60 min to obtain a flexible conductive hydrogel.

9. A fiber-reinforced double-crosslinked network conductive hydrogel and its preparation method according to any one of claims 1-8, characterized in that, The conductive hydrogel has a tensile strength of 0.5-2.0 MPa, an elongation at break of 100%-250%, a compressive strength of 1-1000 kPa, a recovery rate of over 80% after cyclic compression at 50%-90% compressive strain, and an electrical conductivity of 10. -4 -10 S·m -1 It exhibits stable strain response performance, and its relative resistivity change rate remains stable and has good repeatability during cyclic tensile testing.

Citation Information

Patent Citations

  • Degradable electroactive bacterial cellulose / MXene composite hydrogel and preparation method and application thereof

    CN111303449A

  • Photocuring biomass-based dual-network conductive hydrogel and preparation method thereof

    CN118667189A